Retroviral vector insertions in T-lymphocytes used for suicide gene therapy occur in gene groups with specific molecular functions - Giordano, Frank Anton; Fehse, B.; Hotz-Wagenblatt, Agnes; Kogenaru, Sunitha; Val, C. del; Appelt, Jens-Uwe; Nagy, Katalin Zsuzsanna; Kuehlcke, K.; Naundorf, S.; Zander, A. R.; Zeller, W. Jens; Ho, Anthony Dick; et al. (Bone marrow transplantation, 2006)
Graft-versus-host disease (GvHD) is a severe complication in the context of allogeneic stem cell transplantation and adoptive immunotherapy. The transfer of a suicide gene into donor T-lymphocytes (TLCs) allows selective elimination of GvHD-causing cells. As retroviral gene transfer into hematopoietic stem cells can induce leukaemia, there is an urgent need also to analyze retroviral integration sites in TLCs. We examined suicide gene-transduced TLCs in four grafts and from four transplanted patients. One-hundred and fifteen integration sites were detected in vitro. Of these 90 could be mapped to the human genome; 50% (45) were located in genes and 32% (29) were detected 10 kb upstream or downstream of transcription start sites. We found a significant overrepresentation of genes encoding for proteins with receptor activity, signal transducer activity, transcription regulator activity, nucleic acid binding activity and translation regulator activity. Similar data were obtained from patient samples. Our results point to preferred vector integration patterns, which are specific for the target cell population and probably independent of selection processes. Thus, future preclinical analysis of the integration repertoire with abundant amounts of transduced cells could allow a prediction also for the in vivo situation, where target cells are scarce.
Gesehen am 09.11.2021